2009
DOI: 10.2353/ajpath.2009.080602
|View full text |Cite
|
Sign up to set email alerts
|

Renal Ischemia-Induced Cholesterol Loading

Abstract: Acute kidney injury evokes renal tubular cholesterol synthesis. However, the factors during acute kidney injury that regulate HMG CoA reductase (HMGCR) activity, the rate-limiting step in cholesterol synthesis, have not been defined. To investigate these factors, mice were subjected to 30 minutes of either unilateral renal ischemia or sham surgery. After 3 days, bilateral nephrectomy was performed and cortical tissue extracts were prepared. The recruitment of RNA polymerase II (Pol II), transcription factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…A recent study reported recruitment of c-Fos to the Hmgcr promoter for transcriptional regulation under acute kidney injury in mice [43]. The transcription factor n-Myc is a basic helix-loop-helix leucine zipper (bHLH-ZIP) protein that heterodimerizes with the transcription factor Max and play important roles in neuronal differentiation and cell proliferation [44][48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported recruitment of c-Fos to the Hmgcr promoter for transcriptional regulation under acute kidney injury in mice [43]. The transcription factor n-Myc is a basic helix-loop-helix leucine zipper (bHLH-ZIP) protein that heterodimerizes with the transcription factor Max and play important roles in neuronal differentiation and cell proliferation [44][48].…”
Section: Discussionmentioning
confidence: 99%
“…One of the best studied cholesterol biosynthetic promoters is that of the Hmgcr gene (56,57). Hmgcr activity is the ratelimiting step for cholesterol synthesis; consequently, many regulatory molecules affect this gene and gene product as a means of regulating the cholesterol biosynthetic pathway.…”
Section: Figure 8 Egr1mentioning
confidence: 99%
“…In a maleate nephrotoxicity model, renal cortical cholesterol content increased in response to injury along with doubling of HMG CoA reductase (HMGCR) mRNA levels, indicating an increase in synthesis [20,26]. Similarly, in a model of renal IRI, cholesterol loading was associated with elevated recruitment of RNA polymerase II to HMGCR and increased expression of HMGCR protein and mRNA [21,27]. Finally, dysregulation in the cholesterol efflux proteins SR-B1 and ABCA-1 and in LDL receptor was also shown to contribute to a cholesterol overload state in the injured kidney [22,28].…”
Section: Discussionmentioning
confidence: 99%